(untitled) (Research, Society and Development, 2020)
The exchange of amalgam restorations for composite resin occurs for functional or aesthetic reasons. The objective was to carry out a survey of data in the dental records of patients treated at Faculdade Patos de Minas - FPM of quantitative nature aiming to verify the current situation of amalgam restorations that were maintained, repaired, replaced or did not receive any treatment. 250 records were selected randomly, from the 6th to the 10th period, referring to the second half of 2019; the inclusion criteria collected dental records that have amalgam restorations on posterior teeth. Information was collected regarding: Age; Gender; Black’s classification; Treatment: repair, maintenance (finishing and polishing), amalgam exchange or no intervention; As exclusion criteria, medical records that did not present restorations in posterior teeth, under 18 years old. The highest incidence was in adults aged 36-50 years (21.7%). The female gender (52.9%) had a higher number of teeth restored with amalgam. Class I teeth (61.5%) were more affected, followed by class II MO (9.5%), OD (14.6%), or MOD (14.2%). The group without intervention (54.5%) was the recommended procedure. Class I was predominant in tooth 17 (10.6%). Class II MO was predominant in tooth 25 (12.9%), class II OD was predominant in tooth 45 (11.6%), class II MOD was predominant in tooth 26 (10.8%). Regardless of the restorative material, the preservation of the dental structure was maintained, with a greater number of restorations without intervention, instead of maintenance, repair or replacement.